Dual-Action Mechanism of Viramidine Functioning as a Prodrug and as a Catabolic Inhibitor for Ribavirin - Wu, Jim Zhen (American Society for Microbiology, 2004)
An investigational nucleoside analogue drug, viramidine, has recently emerged as a potentially safer alternative to ribavirin for the treatment of hepatitis C viral infection. We have reported that viramidine mainly functions as a prodrug of ribavirin that is enriched in the liver. This in vitro study further explores viramidine's activity against nucleoside phosphorylase, a host enzyme that is responsible for phosphorolysis of ribavirin in vivo. Our experiments show that viramidine inhibits ribavirin phosphorolysis with a K(i) of 2.5 μM. This result suggests that viramidine may act through a dual-action mechanism by serving as a prodrug of ribavirin and concomitantly as an inhibitor for nucleoside phosphorylase catabolism of ribavirin.